Association between aspirin and mortality in critically ill patients with atrial fibrillation: a retrospective cohort study based on mimic-IV database - Zhang, Meijuan; Zuo, Yadong; Jiao, Zhanquan (Frontiers in Cardiovascular Medicine, 2024)
Background Atrial fibrillation (AF) is a prevalent issue among critically ill patients, and the availability of effective treatment strategies for AF is limited. Aim The objective of this study was to evaluate the mortality rate associated with AF in critically ill patients who were either aspirin or non-aspirin users. Methods This cohort study incorporated critically ill patients with AF from the Medical Information Mart for Intensive Care database. The study compared incidences of 28-day mortality, 90-day mortality, and 1-year mortality between patients with and without aspirin prescriptions. To assess the association between aspirin and the endpoints, Kaplan-Meier analysis and Cox proportional hazards regression analyses were conducted. Results In this study, a total of 13,330 critically ill patients with atrial fibrillation (AF) were included, of which 4,421 and 8,909 patients were categorized as aspirin and non-aspirin users, respectively. The 28-day, 90-day, and 1-year mortality rates were found to be 17.5% (2,330/13,330), 23.9% (3,180/13,330), and 32.9% (4,379/13,330), respectively. The results of a fully-adjusted Cox proportional hazard model indicated that aspirin use was negatively associated with the risk of death after adjusting for confounding factors (28-day mortality, HR 0.64, 95% CI 0.55–0.74; 90-day mortality, HR 0.65, 95% CI 0.58–0.74; 1-year mortality, HR 0.67, 95%CI 0.6∼0.74). The results of the subgroup analysis indicate a more robust correlation, specifically among patients under the age of 65 and those without a history of congestive heart failure or myocardial infarction. Conclusions The utilization of aspirin may exhibit a correlation with a reduction in risk-adjusted mortality from all causes in critically ill patients diagnosed with atrial fibrillation. However, additional randomized controlled trials are necessary to elucidate and confirm this potential association.